THE INFLUENCE OF MANAGEMENT MODELS SPECIFICALLY ON WOMEN-ONLY GYMS (Fiep Bulletin - online, 2014)
This surveyispart of the study"Users profileandcharacteristicsofwomen-onlygyms". The understanding of women's perception concerning the market ofwomen-onlygyms constitutes inpertinent instrument oforientation and analysis in order to allow the expansion and improvements in this segment, as well as identify and analyze the assumptions that havesubsidized this process.This study aimed to understand and compare the customers' satisfaction and characteristics of franchised women-only gyms or not ofcities of Zona da Mata region, in Minas Gerais. The sample consisted of 98 women, 66 of the city of the non-franchised gym and 32 of the franchised gym. It was applied a non-validated questionnaire to the gym goers who were disposed to participate of the study, having previously signed an informed consent form. For data analysis, it was used the descriptive statistics of Microsoft Excel program. The study was submitted and approved by Human Research Ethics Committee (HREC) of UFV, have being approved in PlataformaBrasil, registered by CAAE number 16372413.0.0000.5153. In the present study, it was also analyzed the characteristics thatcompose the users profile, testifying that the goers of franchised gyms have a more 'formal' profile than the others. This study testified that despite the use of a management model interferes in the customers' decisions, considering the female public exclusively, those using processes similar to a “ordinary” gym were more satisfied with the services and forms of treatment . It was also verified that the results differ from the results of previous studies, such as Lima and Maffia (2010), concerning the subjects' goals and the environment choice for the physical activity practice.
Keywords: Gym Management; Sedentariness; Physical Activity; Gyms for women; Users profile